Revisiting the Relationship Between Corporate Stakeholder Commitment and Social and Financial Performance. (6th January 2017) - Rivera, Juana M.; Muñoz, Maria J.; Moneva, Jose M.
Abstract: This study delves into the long‐term relationship between social and financial performance of organizations. The aim of this study is to analyse the evolution of this relationship during the global financial crisis to ascertain both how companies have evolved in terms of CSR strategic consistency under financial uncertainty, and the relationship that this consistency may have with their financial performance. A specific methodological approach based on the fuzzy set theory has been applied to the measurement of social and environmental performance over a selected sample of Spanish listed companies, whose CSR strategic consistency had been analysed in previous studies that made use of data published in 2003. The results show a general improvement of CSR strategic consistency among organizations, in spite of a turbulent financial environment. On the other hand, the results show a positive relationship between CSR strategic consistency, and corporate economic and financial performance. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment